TEOLOGI SALIB SEBAGAI PARADIGMA HIDUP KRISTIANI DALAM ERA POSTMODERN - Fanni Srianti Bulawan; Sintia Natalia, Sombo Tasik, Risma Wati Lebok, Yuyun Ravita (ADISAM PUBLISHER, 2025)
This article examines the theology of the cross as a paradigm for Christian life in facing the challenges of the postmodern era, characterized by the relativism of truth, individualism, and the penetration of prosperity theology. This research uses a descriptive qualitative method with a literature study approach, examining various theological and academic sources to explore the relevance of the cross of Christ as the center of faith. The theology of the cross is first understood as a critique of postmodern relativism that rejects absolute truth, affirming the cross as the historical and existential foundation of truth. Second, the cross is understood as an ethic of solidarity and humility, inspiring people to be present for others in a spirit of sacrifice. Third, the cross serves as a foundation for interfaith dialogue in a pluralistic society, presenting the values of reconciliation, peace, and religious moderation. Fourth, the cross serves as a corrective to prosperity theology, which tends to absolutize material success, while also reaffirming faith rooted in love and sacrifice. The results show that the paradigm of the cross offers a relevant spiritual and ethical orientation for the church in building an authentic witness of faith amidst the postmodern current. Thus, the theology of the cross serves not only as a dogmatic framework but also as a practical paradigm that shapes a faithful, humble, and transformative Christian life